Biocompatible Packaging and Testing of an Endocardial Accelerometer for Heart Wall Motion Analysis. (2015) - Brancato, L.; Weydts, T.; De Clercq, H.; Dimiaux, T.; Herijgers, P.; Puers, R.
Abstract: A sensor system for the acquisition of acceleration signals from different locations on the heart wall during acute tests is described. A commercially available miniature three-axis accelerometer is mounted on a small, circular PCB. Three coating layers are applied to ensure the biocompatibility of the sensor: parylene-C, medical grade epoxy and PDMS. The device, intended for use during animal experiments, is shaped as a hemisphere with radius 2 mm. The sensor assembly is a dedicated design that allowsinsertion through the heart wall and fixation on the muscle. A dedicated data acquisition board enables to readout digital acceleration data and ECG signal, and to transmit it wirelessly to a remote receiver. The device was tested in-vitro for electricalisolationand water diffusion. Later, in-vivo performance was evaluated by acquiring acceleration signals from different sites on the cardiac muscle of a sheep.